Potret Keterlibatan Perempuan Dalam Pelayanan Publik di Era Otonomi Daerah - Partini, - (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Gadjah Mada, 2004)
Local bureaucracies has been marginally improved its performance in delivering public service, even though they have been granted with wider autonomy and bureacratic reform has been taking place. Women bureaucrats are not significantly improving the quality of public service as their attitude remain ambivalence, given the persitence of patriarchical culture in local bureaucracy.